1991
DOI: 10.1007/bf01190465
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural organization of the interstitial subnucleus of the nucleus of the tractus solitarius in the cat: Identification of vagal afferents

Abstract: This electron microscopic study, based on serial section analysis, describes the synaptic organization of the interstitial subnucleus of the nucleus of the solitary tract and identifies the terminals of the vagal primary afferents utilizing degeneration and HRP transport. The interstitial subnucleus contains sparsely scattered cell bodies, numerous dendrites and axon terminals, and bundles of unmyelinated and myelinated axons. The cell bodies which are small in diameter have an organelle poor cytoplasm and a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 50 publications
2
19
2
Order By: Relevance
“…Although many axonal profiles in the tractus solitarius did contain high levels of gold labeling, they probably originate from glycinergic projection neurones sited within the medulla or spinal cord. Neither do the observed effects of glycine seem likely to be through presynaptic inhibition of afferent terminals, since such contacts were not observed in the present study, besides which, axo-axonic synaptic contacts have only been rarely observed in most regions of the NTS (Chazal et al, 1991;Chen et al, 1992;Izzo et al, 1992;Maqbool et al, 1991;Saha et al, 1995a). As reported previously for the rat (Cassell et al, 1992), the vast majority of glycine-IR synapses in the NTS contacted small or medium-sized dendritic profiles; therefore, the effects of glycine are most likely brought about via postsynaptic inhibition of interneurones.…”
Section: Distribution and Targets Of Glycine-ir Synapses In The Ntscontrasting
confidence: 71%
“…Although many axonal profiles in the tractus solitarius did contain high levels of gold labeling, they probably originate from glycinergic projection neurones sited within the medulla or spinal cord. Neither do the observed effects of glycine seem likely to be through presynaptic inhibition of afferent terminals, since such contacts were not observed in the present study, besides which, axo-axonic synaptic contacts have only been rarely observed in most regions of the NTS (Chazal et al, 1991;Chen et al, 1992;Izzo et al, 1992;Maqbool et al, 1991;Saha et al, 1995a). As reported previously for the rat (Cassell et al, 1992), the vast majority of glycine-IR synapses in the NTS contacted small or medium-sized dendritic profiles; therefore, the effects of glycine are most likely brought about via postsynaptic inhibition of interneurones.…”
Section: Distribution and Targets Of Glycine-ir Synapses In The Ntscontrasting
confidence: 71%
“…Scale bars: 500 nm (electron micrographs), 400 nm (three-dimensional reconstructions). Chazal et al, 1991;Davis, 1998;Hayakawa et al, 2003;May et al, 2007;Whitehead, 1986). Accordingly, about half of our reconstructed synapses were directly apposed to at least one other synapse without intervening glia.…”
Section: Discussionmentioning
confidence: 93%
“…Studies performed at the cerebellar mossy fiber to granule cells synapse indicate that glutamate spillover in divergent glomeruli enhances the efficacy of fast synaptic transmission by decreasing fluctuations resulting from probabilistic transmitter release (DiGregorio et al, 2002;Sargent et al, 2005). In the NTS, sensory afferent terminals are frequently involved in divergent arrangements (Chazal et al, 1991;Davis, 1998;Hayakawa et al, 2003;May et al, 2007;Whitehead, 1986). One may postulate that glutamate spillover within these synaptic clusters helps to insure reliable transmission of sensory information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saha et al (1995) showed that most glutamatergic terminals in the medial, dorsal, gelatinosus, dorsolateral, and interstitial subnuclei of the NTS of the cat form on dendrites of different sizes. The most numerous synapses in the interstitial subnucleus of the NTS are axodendritic synapses (Glaum and Miller, 1995;Mrini and Jean, 1995), and the terminals of vagal afferents make symmetric and asymmetric contacts with the dendrites in the interstitial subnucleus of the NTS (Chazal et al, 1991). There is some evidence that these terminals are glutamatergic (see discussion in Mrini and Jean, 1995), but immunocytochemical studies at the ultrastructural level are necessary to clarify this point.…”
Section: Distribution In the Nucleus Of The Tractus Solitariusmentioning
confidence: 99%